Ultrasonic inspection of defects in unidirectional composites - Choong, Ming Hwee (Nanyang Technological University, 2021)
This report outlines the defect inspection of thick unidirectional carbon fiber reinforced polymer (CFRP) composites using ultrasonic testing. Although studies have been conducted by other researchers to determine the effectiveness of inspecting composites using ultrasonic testing, many of them focused on the inspection of thin laminates with simple internal structures. However, given that real-world composites tend to be thick and/or have complex internal structures, this presents a research gap to be bridged. Hence, this paper aims to determine the effectiveness of using ultrasonic testing to evaluate the manufacturing and machining qualities of thick composite samples, with complex internal structures including delamination, thick resin layers and side-drilled holes. Three cases were investigated in this study. In Cases 1 and 2, a total of four composite samples were inspected, while Case 3 involved one composite sample. For each case, the raw experimental ultrasonic data obtained was further processed in MATLAB to generate B- and C-scan results. For Case 3, CIVA software was also used to simulate and understand the propagation of ultrasound waves in the tested composite samples. For all three cases, it was found that ultrasonic testing proved capable in identifying the defects. Given the effectiveness of ultrasonic testing in inspecting composite samples, future extension to this study may include the quantitative analysis of fiber waviness profile in composite samples, as well as the investigation of the potential for integrating phased array ultrasonic testing probes or single element transducers in manufacturing or machining tools, to allow in-situ inspection of composite parts while they are being manufactured or machined. This may potentially help manufacturers to reduce material wastage and minimise unnecessary production costs.